Positivity Rate of Stool Antigen of Helicobacter Pylori in Upper Gastrointestinal Endoscopy Duodenitis in Dyspepsia Patients- An Observational Study - M, Malarmannan; Balaji S, Vinith; Dhas A, Pravin; R, Lakshmana; Das, Debarath; N, Soorya (Journal of Neonatal Surgery, 2025)
Introduction: Helicobacter pylori (H. pylori), Gram Negative bacilli, is implicated in diseases such as chronic duodenitis, peptic ulcer, and gastric cancer. While most infected individuals remain symptoms free, a less percentage of individuals may develop peptic ulcer or gastric cancer after prolonged infection, contributing significantly to global morbidity and mortality.In this study we are discussed about the positivity rate of stool antigen of Helicobacter Pylori in upper gastrointestinal endoscopy duodenitis in dyspepsia patients. Objective: To detect the positivity rate of stool antigen of helicobacter pylori in upper gastrointestinal endoscopy duodenitis in dyspepsia patients. To find the sensitivity, specificity, positive predictive value, negative predictive value, disease prevalence and correlation between duodenitis and stool antigen test positivity. Materials And Methods: In this observational study, we included 242 dyspeptic patients and performed an Upper GI endoscopy and Stool Antigen Test ( SAT) using Stool Antigen Test kit,H. pylori antigen is detected for all the patients. Patients who are on Proton pump inhibitors and Any Antibiotic therapy within one month are excluded from this study. Results: In this observational study, by Comparing the age distribution gastritis was more commonly seen in elderly patients > 50yrs and Duodenitis was most commonly seen in middle age group 30-50yrs. Our study has demonstrated results of sensitivity of 96.5% and specificity of 96.1%. Statistically it also shows positive predictive value of 96.5% and negative predictive value of 96.9%, with the disease prevalence of 46.69%. while assessing the chi square value which is 207.225 and p value of 0.0001(<0.05), there is an association between duodenitis and stool antigen test of h.pylori positivity. We have compared our study results with various researches results regarding stool antigen test sensitivity and specificity. Conclusion: Detecting H. pylori infection and resistance for antibiotics are crucial for preventing various gastro-duodenal diseases, including gastric cancer. Stool antigen test was more Efficient , Non invasive and Cost effective and less time consuming than duodenal biopsy in diagnosing H. Pylori infection. Hence H. Pylori treatment could be started at the earliest with this test